Keputusan Pembelian Ditinjau dari Pemasaran TikTok, Citra Merek dan Rating Toko Sinar Kosmetik Sragen - Sari , Vika; Istiatin, Istiatin; Damayanti, Ratna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine and explain the influence of TikTok Marketing, Brand Image and Ratings on Customer Purchasing Decisions of Sinar Cosmetics Sragen. The research method uses quantitative research, in the form of a questionnaire. The population in this study were customers of Sinar Cosmetics Shop, Sragen City, who had made online or offline purchases. Of the 900 populations, 90 respondents were taken as a sample using non-probability techniques. The data used in this study is primary data in the form of questionnaires filled out by respondents. The analytical method used is quantitative analysis, multiple linear regression, F test, t test and the coefficient of determination. Based on these research findings, that TikTok Marketing, Brand Image and Ratings have a positive and simultaneous effect on Purchase Decisions. TikTok Marketing, Ratings have a positive and significant effect on purchasing decisions while Brand Image has no positive and significant effect. Purchasing decisions can be explained by the TikTok Marketing variables, brand image and ratings of 31.5%. From the results of multiple linear regression analysis, it is known that the most dominant variable is TikTok Marketing.